2016
DOI: 10.1080/13876988.2016.1174410
|View full text |Cite
|
Sign up to set email alerts
|

The Role and Impact of the Multiple-Streams Approach in Comparative Policy Analysis

Abstract: John Kingdon's multiple-streams framework has been widely used since the publication of his book Agendas, Alternatives and Public Policies in 1984. The popularity of this agendasetting framework in comparative policy analysis is especially interesting because the book focused exclusively on the United States. It is not clear, however, that a framework developed exclusively on the basis of the examination of a single, somewhat idiosyncratic national case should be able to generate insights useful in comparative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
118
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(124 citation statements)
references
References 28 publications
1
118
0
5
Order By: Relevance
“…Therefore, policy entrepreneurs are not only limited to lobbyists, but could be politicians within or outside the government, interest groups, civil servants, researchers or influential persons who pursue strategies to join the three streams which is not limited to lobbying. Political connections, negotiation and advocacy skills are known to be among several resources they use as the results of the present study also showed.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Therefore, policy entrepreneurs are not only limited to lobbyists, but could be politicians within or outside the government, interest groups, civil servants, researchers or influential persons who pursue strategies to join the three streams which is not limited to lobbying. Political connections, negotiation and advocacy skills are known to be among several resources they use as the results of the present study also showed.…”
Section: Discussionsupporting
confidence: 71%
“…This model highlights the role of interest groups, advocacy groups and policy entrepreneurs within or outside the governments as agents for coupling the three streams. Lobbying is not the core elements of multiple streams theory, as the Kingdon theory contains five structural elements: problems; policies; politics; windows of opportunity and policy entrepreneurs . Therefore, policy entrepreneurs are not only limited to lobbyists, but could be politicians within or outside the government, interest groups, civil servants, researchers or influential persons who pursue strategies to join the three streams which is not limited to lobbying.…”
Section: Discussionmentioning
confidence: 99%
“…Past work has shown that public policy tends to advance during "windows of opportunity" provided by, among other things, focused public attention (12). Without public perception of a problem, the ability of scientific experts and policy analysts to advance a policy agenda will be limited (13). This potentially poses a challenge for addressing chronic environmental problems such as climate change.…”
mentioning
confidence: 99%
“…Although numerous scholars have applied Kingdon's framework to various policy domains (Pierce et al 2014, Béland andHowlett 2016), it has seen limited application in child welfare (Collins and Clay 2009 is an exception). While widely used, the framework has been critiqued for having such fluidity that it lacks explicit hypotheses (Sabatier, 2007) and for its limited predictive capabilities (Zahariadis, 1999).…”
Section: Theoretical Frameworkmentioning
confidence: 99%